Laporan Tugas Prarancangan Pabrik Prarancangan Pabrik Asam Asetatdengan Proses Monsanto Kapasitas 100.000 Ton Per Tahun - Mardian Hastungkoro, Syifda Riyandi Wahyu; , Hamid Abdillah, S.T., M.T; , Emi Erawati, S.T,. M.Eng (2017)
Acetic acid plant with a designed production capacity of 100,000 tons per year with the raw material of methanol and carbon monoxide. The plant will be established in an industrial area Bontang, East Kalimantan, with a land area of 25,000 m2, and the number of employees 160 people. Factories operated continuously for 330 days per year. The process of manufacture of acetic acid made in the bubble reactor with cooling water. The reaction takes place in the liquid-gas phase, the nature of the exothermic reaction, irreversible, isothermal operating conditions, non-adiabatic at a temperature of 177oC and at a pressure of 30 atm. This plant requires is 6,779.95 kg of methanol per hour and carbon monoxide is 6,024.49 kg per hour to produce acetic acid is 12,626.26 kg per hour. Utilities include the provision of water extracted from the river, the water needs 561,028.661 kg per hour, the provision of 951.23 kg per hour of steam obtained from the boiler with fuel oil is 451.78 liters per hour and compressed air is 50 m3 per hour. The demand for electricity obtained from the PLN and 350 kW generator set as a backup. The acetic acid plant uses Rp 682,197,984,948 of fixed capital and working capital Rp 386,313,061,457. From the results of the economic analysis, this plant showed pre-tax profits Rp 296,050,149,313 per year and after tax Rp 148,025,074,656 per year. Percent Return On Investment (ROI) before tax is 43.39% and after tax 21.69%. Pay Out Time (POT) before taxes for 1.87 years and 3.15 years after tax. Break Event Point (BEP) amounted to 41.84%, Shut Down Point (SDP) amounted to 29.85%, and Internal Rate of Return (IRR) of 34.01%.